(untitled) - Olejniczak, Maja (Harlow, 2011)
The Pearson Longman Vocational English series is designed to meet the English language needs of learners in a range of vocational specializations. Designed for both pre-work and in-work learners these titles combine a strong grammar syllabus with the essential vocabulary that these students will need in their working lives.
Keywords: Information technology,Công nghệ thông tin; Terminology,Study and teaching,Thuật ngữ,Dạy và học